The train-watcher's guide to north American railroads (Kalmbach Books, 1992)
Some industries are more satisfying to watch than others. Transportation is close to the top of the list - whe did you last see someone enthralled by a librarian reshelving books or encounter a collection of photos of insurance agencies?...